Trump's foreign policy and NATO: Exit and voice. Issue 3 (July 2019) - Sperling, James; Webber, Mark
Abstract: Donald Trump assumed office in January 2017, committed to revamping US foreign policy and putting 'America First'. The clear implication was that long-held international commitments would be sidelined where, in Trump's view, the American interest was not being served. NATO, in the crosshairs of this approach, has managed to ride out much of the criticism Trump has levelled against it. Written off as 'obsolete' by the American president, it has fared better in the Trump era than many commentators had predicted. NATO exemplifies a tendency in US foreign policy, which pre-dates Trump, where open criticism stops short of abandonment. This pattern has continued since 2017 and indicates a preference for voice over exit. As such, it suggests that Trump's foreign policy is not always as illogical as many have assumed. Logic is borne of institutional context: Trump has chosen to articulate voice where institutionalisation makes exit unviable. Institutional resilience in general and NATO's case specifically has a wider relevance, both for transatlantic relations and international order.